2004
DOI: 10.1128/mcb.24.19.8716-8726.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin-Conjugating Enzyme UBCH7 Acts as a Coactivator for Steroid Hormone Receptors

Abstract: We investigated the role of the ubiquitin-conjugating enzyme UBCH7 in nuclear receptor transactivation. Using transient transfection assays, we demonstrated that UBCH7 modulates the transcriptional activity of progesterone receptor (PR) and glucocorticoid, androgen, and retinoic acid receptors in a hormone-dependent manner and that the ubiquitin conjugation activity of UBCH7 is required for its ability to potentiate transactivation by steroid hormone receptors (SHR). However, UBCH7 showed no significant effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 65 publications
3
50
1
1
Order By: Relevance
“…This interaction enhanced their transcriptional activities. Moreover, UbcH7 modulated nuclear receptor transactivation, including GR function, by interaction with the co-activator SRC-1 (Verma et al 2004). Independently, we identified UbcH7 as the physical interacting partner of the GR in a yeast two-hybrid screen.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…This interaction enhanced their transcriptional activities. Moreover, UbcH7 modulated nuclear receptor transactivation, including GR function, by interaction with the co-activator SRC-1 (Verma et al 2004). Independently, we identified UbcH7 as the physical interacting partner of the GR in a yeast two-hybrid screen.…”
Section: Introductionmentioning
confidence: 85%
“…This may reflect altered stability of the GR or its interactions with other proteins in the absence of authentic UbcH7 activity. For example, UbcH7 has been shown to interact with GR co-modulator proteins, and may be important for stabilizing the GR, or its interactions with UbcH7 (Verma et al 2004). By inhibiting the enzymatic activity of endogenous UbcH7 on these partner proteins, the dominant negative UbcH7 may stabilize interactions between the GR and the UbcH7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A ubiquitinconjugating enzyme (E2) also may be part of the coactivator complex (40). One report showed that an E2, UbcH7, interacts with SRC-1 to regulate the transcriptional activity of NRs (41). Such an interaction between ER␣ and an E2 may be necessary for Smad degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Uba3-an ubiquitin-activating enzyme of the NEDD8 pathway, have all been reported to act as coactivators for NHRs (16, 20 -22). Our laboratory has recently demonstrated yet another ubiquitin-conjugating enzyme, UbcH7 which also acts as a coactivator and enhances the transcriptional activity of NHRs (17). Other examples of dual function proteins are the coactivator p300, which is known to possess intrinsic E3 ligase as well as HAT activities and the general transcription factor TAFII250, which has an intrinsic ubiquitin-conjugating activity (23,24).…”
Section: Coactivatorsmentioning
confidence: 99%